1982
DOI: 10.1111/j.0954-6820.1982.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P‐Component and C‐Reactive Protein in Serum of Healthy Icelanders and Members of an Icelandic Family with Macroglobulinaemia

Abstract: ABSTRACT. Serum levels of amyloid P‐component (SAP) and C‐reactive protein (CRP) were determined in 260 asymptomatic Icelanders of both sexes and various age groups and in 60 members of a family with macroglobulinaemia. In the normal group the SAP levels were normally distributed but slightly higher than in a comparable British group. Elevated levels of SAP and CRP were found in four elderly sibs of the macroglobulinaemia family. Two of them had benign monoclonal macroglobulinaemia (BMM), one had Waldenström'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Population-based cross-sectional surveys dealing with clinical correlations of CRP are few, not to mention longitudinal studies. Thus, it is not known to what extent a persistently raised CRP level can be a sign of an occult disease (8).…”
Section: Discussionmentioning
confidence: 99%
“…Population-based cross-sectional surveys dealing with clinical correlations of CRP are few, not to mention longitudinal studies. Thus, it is not known to what extent a persistently raised CRP level can be a sign of an occult disease (8).…”
Section: Discussionmentioning
confidence: 99%
“…Human SAP is not an acute phase reactant although in chronic inflammatory conditions, in which there is sustained increased production of CRP, SAP values tend to be slightly higher, albeit within the reference range 21 . A few small studies in the elderly and subjects with impaired cognition have reported plasma and CSF SAP concentrations above the reference range of the healthy middle aged population 2,22,23,24 . Children under 10 years have circulating SAP concentrations below the adult range but reduced adult SAP values are seen only with severe hepatocellular impairment 21 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Human SAP is not an acute phase reactant although in chronic inflammatory conditions, in which there is sustained increased production of CRP, SAP values tend to be slightly higher, albeit within the reference range [ 21 ]. A few small studies in the elderly and subjects with impaired cognition have reported plasma and CSF SAP concentrations above the reference range of the healthy middle-aged population [ 2 , 22 24 ]. Children under 10 years have circulating SAP concentrations below the adult range but reduced adult SAP values are seen only with severe hepatocellular impairment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%